Diurnal High Temperatures Affect the Physiological Performance and Fruit Quality of Highbush Blueberry (Vaccinium corymbosum L.) cv. Legacy - Jorge González-Villagra; Kevin Ávila; Humberto A. Gajardo; León A. Bravo; Alejandra Ribera-Fonseca; Emilio Jorquera-Fontena; Gustavo Curaqueo; Cecilia Roldán; Priscilla Falquetto-Gomes; Adriano Nunes-Nesi; Marjorie M. Reyes-Díaz (Plants, 2024)
In this study, the physiological performance and fruit quality responses of the highbush blueberry (Vaccinium corymbosum) cultivar Legacy to high temperatures (HTs) were evaluated in a field experiment. Three-year-old V. corymbosum plants were exposed to two temperature treatments between fruit load set and harvest during the 2022/2023 season: (i) ambient temperature (AT) and (ii) high temperature (HT) (5 °C ± 1 °C above ambient temperature). A chamber covered with transparent polyethylene (100 µm thick) was used to apply the HT treatment. In our study, the diurnal temperature was maintained with a difference of 5.03 °C ± 0.12 °C between the AT and HT treatments. Our findings indicated that HT significantly decreased CO2 assimilation (Pn) by 45% and stomatal conductance (gs) by 35.2% compared to the AT treatment. By contrast, the intercellular CO2 concentration (Ci) showed higher levels (about 6%) in HT plants than in AT plants. Fruit quality analyses revealed that the fruit weight and equatorial diameter decreased by 39% and 13%, respectively, in the HT treatment compared to the AT treatment. By contrast, the firmness and total soluble solids (TSS) were higher in the HT treatment than in the AT treatment. Meanwhile, the titratable acidity showed no changes between temperature treatments. In our study, Pn reduction could be associated with stomatal and non-stomatal limitations under HT treatment. Although these findings improve our understanding of the impact of HTs on fruit growth and quality in V. corymbosum, further biochemical and molecular studies are need.